2022
DOI: 10.3389/fnhum.2022.924155
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Brain-Derived Neurotrophic Factor Signaling in Central Nervous System Disease Pathogenesis

Abstract: Recent studies have found abnormal levels of brain-derived neurotrophic factor (BDNF) in a variety of central nervous system (CNS) diseases (e.g., stroke, depression, anxiety, Alzheimer’s disease, and Parkinson’s disease). This suggests that BDNF may be involved in the pathogenesis of these diseases. Moreover, regulating BDNF signaling may represent a potential treatment for such diseases. With reference to recent research papers in related fields, this article reviews the production and regulation of BDNF in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…We also examined NPC module 4 as it is associated with gene expression and transcription pathways and found that BDNF and RPE65 are involved in this module. BDNF, stimulates intracellular signaling and controls neurogenesis that is critical for neuronal survival, morphogenesis, and plasticity, and has connections with 45 genes in this module. No notable change was observed in the expression level of the BDNF.…”
Section: Resultsmentioning
confidence: 99%
“…We also examined NPC module 4 as it is associated with gene expression and transcription pathways and found that BDNF and RPE65 are involved in this module. BDNF, stimulates intracellular signaling and controls neurogenesis that is critical for neuronal survival, morphogenesis, and plasticity, and has connections with 45 genes in this module. No notable change was observed in the expression level of the BDNF.…”
Section: Resultsmentioning
confidence: 99%
“…When myostatin activation is elevated, such as during COVID-19 infection, the SMAD complexes become less unavailable to the BMPs, and the skeletal muscles lose proteins. Taken together, all events during new onset acute sarcopenia in COVID-19 infection induced muscular autophagy via increased mitochondrial dysfunction and decreased mitochondrial biogenesis, which decreases skeletal muscles synthesis and increases not only myofibrillar breakdown but also skeletal muscles degradation [18,[140][141][142].…”
Section: Myostatinmentioning
confidence: 99%
“…In the substantia nigra, BDNF might also improve the differentiation and survival of dopaminergic neurons [ 284 ]. Moreover, BDNF has a significant contribution in memory, synaptic plasticity, and neuronal survival [ 285 ]. Various small molecules have been developed that have the capacity to target BDNF receptors [ 286 , 287 ].…”
Section: Antiapoptotic Agents In the Treatment Of Neurodegenerative D...mentioning
confidence: 99%